GNSS maps in environmental monitoring - Awange, Joseph (2018)
© Springer International Publishing AG 2018. Traditionally, maps have been produced by plotting features on paper at a given scale, calling upon a variety of cartographic skills. The advent of computers, satellite data, and geographical information system (GIS), however, has revolutionized the art of map production, with the modern day cartographer required to master computer skills for the purpose of not only the production, but also the management of digital maps.